2013
DOI: 10.1097/brs.0b013e3182a8c488
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Phenomenon of Vertebral Refractures After Percutaneous Vertebroplasty in a Patient With Glucocorticosteroid-Induced Osteoporosis

Abstract: The use of PVP as a therapeutic alternative for the treatment of VCFs in patients with GIOP is still controversial. As seen in our case, even when the management decisions were made in consideration of the patient's pulmonary infection, the outcome was disastrous with the cluster phenomenon of vertebral refractures. Current findings suggest a compelling need for high-quality studies investigating cement augmentation procedures in patients with VCF with GIOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous work showed PVP and PKP may induce vertebra refracture after a long time such as one year, which is commonly associated with solid or trabecular cement pattern. [ 24 , 25 ] Therefore, mixed cement pattern is preferred for the treatment of VCFs. Compared with PVP and PKP treatments, PMCP treatment had a controlled cement pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed PVP and PKP may induce vertebra refracture after a long time such as one year, which is commonly associated with solid or trabecular cement pattern. [ 24 , 25 ] Therefore, mixed cement pattern is preferred for the treatment of VCFs. Compared with PVP and PKP treatments, PMCP treatment had a controlled cement pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, new fractures of L1 may have occurred during the 18 months after vertebroplasty, when the patient no longer received intervention treatment, such as immobilization or surgery. Sun et al [15] reported 3 new fracture signs on the other side of the previously augmented bodies in their case report.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature from January 1, 1995, to December 1, 2013, was conducted for relevant studies about PVP or PKP regarding glucocorticosteroid-induced osteoporotic vertebral compression fractures in the PubMed database. One hundred and seventeen patients with GIOPVCFs treated by PVP or PKP were included in the 11 eligible studies ( 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ). Fifty of 117 (42.8%) patients sustained refractures after vertebropalsty and received repeated vertebroplasty procedures, of which 24 and 26 patients underwent PKP and PVP procedures, respectively.…”
Section: Discussionmentioning
confidence: 99%